Shirinov, Bashar - (:unkn) unknown (My University, 2026)
Bashar Habib oglu Shirinov graduated with honors from the Azerbaijan University of Architecture and Construction (AzUAC), earning a Bachelor’s degree in Management in 2001 and a Master’s degree in Business Organization and Management in 2003. He began his academic career in 2003 as a part-time Lecturer at the Department of Economics and Management of Service Sectors at AzUAC. From 2005 to 2011, he worked as a Lecturer at the Department of Business Economics and Management and served as a Senior Lecturer from 2011 to 2024. In 2017, he was awarded the degree of Doctor of Philosophy (PhD) in Economics in the specialty 5312.01 – Industrial Economics. His dissertation focused on ways to improve the efficiency of working capital utilization in construction enterprises in Azerbaijan. Since 2024, Dr. Shirinov has been serving as an Associate Professor at the Department of Business Economics and Management at AzUAC. He is the author of one textbook, 72 scientific articles, 58 conference papers, and 26 course programmes.